Multi-stage optimization framework for the real-time truck decision problem in open-pit mines: a case study on Sungun copper mine. Issue 7 (9th August 2022) - Mohtasham, Mehrnaz; Mirzaei-Nasirabad, Hossein; Askari-Nasab, Hooman; Alizadeh, Behrooz
ABSTRACT: This work deals with the optimal decisions for materials handling in open-pit mines. The main purpose of this research is to present a multi-stage approach, which has three sequential stages: (a) fleet size selection stage, (b) fleet allocation stage, and (c) real-time truck dispatching stage. At first, a simulation-based optimisation method is provided to evaluate the optimal number of trucks. Then, a new heuristic algorithm is developed for making operational decisions. To evaluate the performance of the proposed framework, the dispatching algorithm used by Modular Mining DISPATCH is developed. The results indicate that the proposed method yields fairly good performance.